Retrospective study on antibody response to vaccination of the African buffalo (Syncerus caffer) and roan antelope (Hippotragus equinus) with Clone 13 Rift Valley fever virus vaccine - Venter, Estelle Hildegard (University of Pretoria, 2018)
Dissertation (MMedVet)--University of Pretoria, 2017.